Dependence Severity and Locus of Control Among Male Alcoholic Clients: A Correlational Study - Wuod A. Hasan, Qahtan Q. Mohammed (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Worldwide, Alcohol is the most generally abused substances, In Americans society, approximately 8.5 percent over 18 years old have an alcohol use disorder, in Iraq about 291in patient and 2990 outpatient male for the purpose of addiction treatment, that’s number and increased statistics about alcohol use lead us to study the possible causes and may be the way to get treatment by studying the locus of control and the dependence severity of alcohol. Aims: To assess the level of dependence severity, locus of control in male alcoholic clients. To measure the correlation among dependence with locus of control in male alcoholic clients. To find out the relationship between locus of control and client socio-demographic variables (age, education, employment and marital status) and clinical features (amount, duration, type of current admission, number of admission). Methodology: A descriptive correlational design. A non-probability, purposive Sample of (70) clients. This study started from November/2021 to march/2022. Result: the results show that 40% of alcoholic male clients with age group 30-39 years old who are urban residency 92.9%, 57.2% married, 41.4% of them are primary school, and 47.1% of them are employee, with sufficient monthly income 41.4%. With regard to duration of alcohol use 27.1% is reported 6-10 years on alcohol and 24.3% are seen among those with 1-5 years and 11-15 years duration and in relation to amount the finding refers that 47.1 of clients are consumed more than one litter per day of more than one type (42.9%). The majority of them reported they admitted to hospital spontaneously (voluntary admission) 97.1%.for first time 65.7%. Male alcoholic clients show moderate dependency on alcohol. Showing low to moderate internal locus of control and moderate to high external locus of control. Dependence severity is associated with internal and external locus of control; the internal and external locus of control are associated with monthly income. Conclusion: alcoholic male clients have a moderately dependence on alcohol, and the external locus of control are more dominant in their drinking behaviour.